SOME QUESTIONS OF METHODOLOGY OF SCIENTIFIC RESEARCH OF LEGAL EXAMINATION OF LEGAL ACTS - Рибікова, Ганна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: a reasonable choice of methods and techniques for studying the phenomenon of legal examination of regulations both in Ukraine and in leading countries. Research methodology: in the work the dialectical method of cognition, general scientific and special methods was used. Findings: a list of methods is proposed, which together allow to achieve the goal of clarifying the theoretical and practical foundations of the organization and functioning of legal examination of regulations. Discussion: search for modern theoretical and methodological approaches to the study of problems of legal examination of regulations. In modern theory of law, methodology is defined as the theoretical basis and methods of organizing the cognitive process, which determine the logical sequence of scientific research, cover the doctrine of a system of scientific concepts, ideas, methods, logical techniques and principles of knowledge of general and specific patterns of origin, structure, development and functioning. The methodology of research of legal examination of normative legal acts can be defined as a system of theoretical, obtained as a result of research knowledge, views, ideas and methods of their implementation, aimed at forming ideas about the legal nature of the process of checking normative legal acts by experts. The characteristic of the methodology of research of problems of legal examination of legal acts is based on the grounded system of methods of knowledge of this legal phenomenon. The research of methodological bases of legal examination of legal acts should also be carried out taking into account such methodological approaches of modern jurisprudence as natural-legal, positivist and sociological. With the help of methodology we can correctly determine the role and place of legal examination of legal acts in dynamic and complex law-making processes, identify objective patterns of its development, determine its elemental composition. In our opinion, the general research methods of the institute of legal examination of legal acts should include general scientific methods (comparison, generalization, analysis, etc.). Special methods of scientific research in this field include comparative law, system-structural, formal law, hermeneutic, prognostic and other methods.